ChemInform Abstract: An Efficient Synthesis of 7‐Methoxy‐1‐naphthylacetic Acid. Issue 16 (22nd April 2014) - Chinea, Kimberly; Vera, William J.; Sanchez, Jennifer; Banerjee, Ajoy K.
Abstract The product is obtained in higher yield (89%) than the previously reported method.